The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1203/pdr.0b013e3181f2edd2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass in Rett Syndrome: Association with Clinical Parameters and MECP2 Mutations

Abstract: Rett Syndrome (RTT) is an X-linked neurodevelopmental disorder caused by mutations in the MECP2 gene. In 49 female RTT children, ages 1.9–17 years, bone mass was assessed and correlated with clinical parameters and mutations involving the MECP2 gene. We also studied 5 adult females, ages 20–33 years, and one male, age 6 years. Lumbar spine bone mineral content (BMC) and bone mineral density (BMD) were correlated with weight, height, body mass index, clinical severity, degree of scoliosis, use of anticonvulsant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 29 publications
3
28
2
Order By: Relevance
“…172,173 Fracture risk was four times that of the general female population, and specifically increased in those with p.Arg168* and p.Arg270*mutations (see Fig 2). 173 Several Danish, 174,175 US 176,177 and further Australian studies 178,179 have also investigated which particular bone parameters were most adversely affected and their potential nutritional, 180 (e.g. Vitamin D status) environmental and genetic risk factors.…”
Section: Bone Healthmentioning
confidence: 99%
“…172,173 Fracture risk was four times that of the general female population, and specifically increased in those with p.Arg168* and p.Arg270*mutations (see Fig 2). 173 Several Danish, 174,175 US 176,177 and further Australian studies 178,179 have also investigated which particular bone parameters were most adversely affected and their potential nutritional, 180 (e.g. Vitamin D status) environmental and genetic risk factors.…”
Section: Bone Healthmentioning
confidence: 99%
“…However, in general, studies have reported conflicting associations of the effects of physical activity on bone turnover in different populations (37). Also, DXA studies of the association between bone mass and ambulant ability in RTT have shown diverging results (4,6,7,13,38).…”
Section: Rett Syndrome and Low Bone Turnovermentioning
confidence: 99%
“…Apraxia or motor planning difficulty interferes with nutritional intake (chewing and swallowing) as well as mobility. The exact effect of the MeCP2 protein on bone formation is not yet understood, but central control of bone remodeling is involved at the level of the osteoblast [45][46][47]. On a cellular level, Budden et al [48] explored the etiology behind the low bone mass observed using bone histomorphologic studies in 5 girls with Rett syndrome requiring orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 99%